2009
DOI: 10.1007/978-3-642-04568-4_21
|View full text |Cite
|
Sign up to set email alerts
|

For a Methodology to Implement Virtual Breeding Environments – A Case Study in the Mold and Die Sector in Brazil

Abstract: Abstract. This paper addresses the general problem of how classical cluster of industries can become a Virtual Breeding Environment (VBE). Using reference frameworks and models, a methodology to support this evolution is being conceived and its preliminary results are presented. This work tackles a cluster of moulds and dies industries from Brazil as the basis for the research and propositions. In the future, this methodology intends to serve as a concrete mean to systematize the implementation of a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Several works have addressed the problem related to model CNOs. A comprehensive review of the state-of-the-art about such subject is found in Baldo and Rabelo [4]. In this work, the authors state that ARCON modeling framework is suitable enough to model VBEs and can be used to model a VBE for an industrial clusters.…”
Section: Vbe Specificationmentioning
confidence: 96%
See 1 more Smart Citation
“…Several works have addressed the problem related to model CNOs. A comprehensive review of the state-of-the-art about such subject is found in Baldo and Rabelo [4]. In this work, the authors state that ARCON modeling framework is suitable enough to model VBEs and can be used to model a VBE for an industrial clusters.…”
Section: Vbe Specificationmentioning
confidence: 96%
“…This model classifies every element necessary to design the NuFerJ VBE, which in turn will guide the work towards its implementation. Baldo and Rabelo [4] presents the VBE model created specifically for NuFerJ, considering all involved elements in the Endogenous and Exogenous ARCON's subspaces [7].…”
Section: Vbe Specificationmentioning
confidence: 99%
“…Nowadays the VBE toolkit is currently being used in the Nuferj Network (Group of Moulds and Dies Industries of Joinville, Brazil) to transform this classical cluster of industries into a state-of-the-art Virtual Organisation Breeding Environment (VBE), proving in a real practical sense the contribution of this toolkit for the industry (Baldo and Rabelo 2009).…”
Section: Vbe Toolkit Validationmentioning
confidence: 99%
“…Several works have addressed the problem related to model CNOs. A comprehensive review of the state-of-the-art about such subject is found in Baldo and Rabelo [8]. In this work, the authors state that among the reviewed CNO modeling frameworks, ARCON is the most appropriated one to model VBEs for industry clusters.…”
Section: Vbe Model Specificationmentioning
confidence: 99%
“…This model classifies every element necessary to design the NuFerJ VBE, which in turn will guide the work towards its implementation. Baldo and Rabelo [8] presents the VBE model created for NuFerJ, considering all the characteristics and elements involved in the Endogenous and Exogenous ARCON's subspaces [11].…”
Section: Vbe Model Specificationmentioning
confidence: 99%